2014
DOI: 10.1007/s00420-014-0930-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial working conditions and psychological well-being among employees in 34 European countries

Abstract: A large number of psychosocial work factors were associated with poor well-being. Almost no country and occupational differences were found in these associations. This study gave a first European overview and could be useful to inform cross-national policy debate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
111
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(132 citation statements)
references
References 48 publications
12
111
2
7
Order By: Relevance
“…Our results corroborate findings from prospective studies on the active work force which have reported health-effects of job insecurity in up to 9.5 years (on average) of follow-up (1,7,9,10). The size of the effect observed in our study was comparable to that reported in the latest cross-sectional European study on the association between job insecurity and SWB (17). Concerning the underlying mechanisms of our findings, job insecurity is considered to be a work-related stressor which can induce physiological or mental arousal (2).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results corroborate findings from prospective studies on the active work force which have reported health-effects of job insecurity in up to 9.5 years (on average) of follow-up (1,7,9,10). The size of the effect observed in our study was comparable to that reported in the latest cross-sectional European study on the association between job insecurity and SWB (17). Concerning the underlying mechanisms of our findings, job insecurity is considered to be a work-related stressor which can induce physiological or mental arousal (2).…”
Section: Discussionsupporting
confidence: 91%
“…SWB was assessed at follow-up using the World Health Organization (WHO)-5 Well-Being Index (26) and dichotomized for reasons of comparability with other studies [eg, (17)]. Following WHO recommendations, participants with a sum score of ≤50 were defined as having low SWB (19,27,28).…”
Section: Measures At T2mentioning
confidence: 99%
See 2 more Smart Citations
“…Emotions can be saved, with interest and excitement ' drawn back' and retained for future purposes. Interesting enough, one psychosocial work factor found to be associated with poor employee well-being is the demand for emotions to be hidden (Schütte et al, 2014). In the context of fixed-term contracts, these demands are related to the restricted and obscured time-span, which forces employees to anticipate loss and a lack of involvement while performing, thus detaching themselves.…”
Section: Regulating and Hiding Emotionsmentioning
confidence: 99%